The Effect of Training and Work Discipline on the Performance of Civil Servants with Work Motivation as an Intervening Variable in the Government of Sorong City - Josina I.D; Septinus B.K (Proceeding of The International Conference on Business and Economics, 2026)
Civil servants (Aparatur Sipil Negara/ASN) play a strategic role in government administration and public service delivery; therefore, improving their performance is essential to achieving effective and accountable governance. This study aims to analyze the effect of training and work discipline on ASN performance, with work motivation as an intervening variable, in the Government of Sorong City. A quantitative approach was employed using a survey method. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that training and work discipline have a positive and significant effect on work motivation. Furthermore, training, work discipline, and work motivation positively and significantly affect ASN performance. Work motivation is proven to mediate the relationship between training and work discipline on ASN performance. These findings suggest that improving ASN performance can be achieved through strengthening training quality, enforcing work discipline, and enhancing work motivation simultaneously.